IMPLEMENTATION OF PSAK 412 WAQF ACCOUNTING AND FINANCIAL STATEMENTS AT WAQF MULIA INSTITUTE - Ibnu Hajar; Suciyanti Suciyanti (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study critically evaluates the implementation of PSAK 412 (Waqf Accounting Standard) by a national-scale nazhir, the Waqf Mulia Institute (WMI), focusing on achieving substantial transparency and accountability in waqf asset management. Employing a qualitative, holistic single case study design, the research analyzed WMI's 2023–2024 financial statements and primary data from management interviews, comparing their practices against the four pillars of PSAK 412: Recognition, Measurement, Presentation, and Disclosure. Findings reveal high compliance in Presentation and Disclosure, with WMI providing all five mandatory financial statements comprehensively; however, a significant implementation gap exists in Measurement. Despite management's claim of using fair value, evidence—such as a nil value in the "Impact of Remeasurement of Waqf Assets" line item and the continued dominance of the historical cost basis—shows that periodic remeasurement of non-cash assets is not systematically executed, indicating that while WMI is mature in formal reporting, it still faces technical and cost constraints in fully implementing the fair value principle for non-cash assets as strictly required by PSAK 412.